2020
DOI: 10.1002/jcb.29671
|View full text |Cite
|
Sign up to set email alerts
|

The timing of propofol administration affects the effectiveness of remote ischemic preconditioning induced cardioprotection in rats

Abstract: The cardioprotection of remote ischemic preconditioning (RIPC) is abolished under propofol maintained anesthesia. Transient receptor potential vanilloid 1 (TRPV1) channel is present in the heart, and its activation could induce cardioprotection. Therefore, we tested whether the anesthetic propofol administration phase interfered with the RIPC‐induced cardioprotection, and RIPC‐induced cardioprotection via the cardiac TRPV1 channel. Male Sprague‐Dawley rats were subjected to myocardial 30 minutes of ischemia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In fact, some recently published experimental studies suggest that the potential interaction between these factors, such as propofol, with organ protective efficacy of RIPC may be more complicated than expected. A recent study in a rat model found that the timing of propofol administration could affect RIPC-induced cardioprotection (45), and that different doses of propofol used in the studies may have also affected the results. Future studies are needed to determine the influences of patient characteristics, procedure, perioperative drugs, and RIPC protocol on the efficacy of RIPC on AKI prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some recently published experimental studies suggest that the potential interaction between these factors, such as propofol, with organ protective efficacy of RIPC may be more complicated than expected. A recent study in a rat model found that the timing of propofol administration could affect RIPC-induced cardioprotection (45), and that different doses of propofol used in the studies may have also affected the results. Future studies are needed to determine the influences of patient characteristics, procedure, perioperative drugs, and RIPC protocol on the efficacy of RIPC on AKI prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Abel et al reported that extracellular microvesicles isolated from patients undergoing RIPC vs sham were associated with decreased hypoxia-evoked apoptosis of cardiomyoblasts after iso urane --but not propofol exposure [15,38]. Yu et al [39], in a rodent model, suggested that propofol blunts the cardioprotective effect of RIPC through its effect on the cardiac TRPV1 channel only if it is administered before RIPC, but not when propofol is given after RIPC [40]. Thus, the effect of propofol on RIPC remains an unresolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Abel et al reported that extracellular microvesicles isolated from patients undergoing RIPC versus sham were associated with decreased hypoxia-evoked apoptosis of cardiomyoblasts after isoflurane – but not after propofol 15 , 38 . Yu et al 39 , in a rodent model, suggested that propofol blunts the cardioprotective effect of RIPC through its effect on the cardiac TRPV1 channel only if it is administered before RIPC, but not when propofol is given after RIPC 40 . Thus, the effect of propofol on RIPC remains an unresolved issue.…”
Section: Discussionmentioning
confidence: 99%